(untitled) (Advances in Applied Biological Research, 2025)
An assessment of Tinospora cordifolia extract’s (TCE) antimicrobial and antioxidant properties was undertaken in light of its possible application as cytotoxic against HCT116. Compounds from the stem were Soxhlet extracted with ethyl acetate and identified through GCMS. Antibacterial, antioxidant and HCT cytotoxicity of extract was studied by conventional standard methods. The GC–MS profile highlights a chemically diverse phytochemical composition, with both major and minor compounds potentially responsible for natural antimicrobial and antioxidant agent. The extract has broad spectrum antibacterial activity at concentration dependent manner against both Gram positive and negative clinical pathogens with relative inhibition 83 to 107%. Among the tested antioxidant assay the extract showed the strongest DPPH scavenging with an IC₅₀ value of 12.07 µg/mL, which, although higher than the standard ascorbic acid. Treatment of HCT116 colorectal carcinoma cells with TCE resulted in a dose-dependent reduction in cell viability. Nonlinear regression analysis of the MTT assay revealed an IC₅₀ value of 359 µg/ml, with viability decreasing from 80% at 300 µg/ml to <10% at 900–1000 µg/ml. Morphological examination and apoptosis assays further confirmed that cell death was predominantly apoptotic nature of cancerous cells. The molecular docking of compounds 2-Fluoro-3-trifluoromethylbenzoic acid found to be strongest binding affinity and non-toxic drug likeness identified as promising new anticancer compound.